Segurança privada - Azevedo, Diogo António Marques Rodrigues Dias (2022)
This dissertation aims to make a comparison between the constitutional framework of public security of the Portuguese legal system, with the public security sector (and its organic structure) of the Macau Special Administrative Region, more specifically, it aims to reflect on a comparative legal analysis between the legal regimes of private security of both legal systems. Taking into account this comparative contrast, this work has the primary objective of suggesting possible innovation measures for the private security legal regime of the Macao SAR.